HUBUNGAN KEPATUHAN MINUM OBAT DENGAN KUALITAS HIDUP PENDERITA Tb MDR di POLI Tb MDR RSUD ARIFIN AHMAD PEKANBARU - Dian Purnama Sari; Darwin Karim; Juniar Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Multiple Drug Resistance Tuberculosis is Mycobacterium Tuberculosis which is minimally resistant torifampicin and isoniazid, both of them are very important drugs in medication of Tb that are applied tothe DOTS strategy. This study aimed to find out the relationship of medication adherence to the qualityof life of MDR Tb patients in poly Tb-MDR RSUD Arifin Ahmad Riau Province by applying thedescriptive correlational research design and cross-sectional approach. The sample of the research was47 respondents were taken based on the inclusion criteria using purposive sampling technique. Theinstruments used were Morizky Medication Adherance Scale-8 (MMAS-8)questionnaires for medicationadherence variable and WHOQOL BREF for the quality of life variable. The study was analyzed byusing univariate analysis to know the frequency distribution and bivariate analysis which used chisquaretest. The results showed 33 respondents had high adherence (70.2%) and as much as 14respondents who had low adherence (29.8%). Respondents with high quality of life were 26respondents (55.3%) and 21 respondents had low quality of life (44.7%). Average high quality of life onhigh adherencewas 66,70%, low quality of life on high adherence was 33,30%, high quality of life onlow adherence was 28,60% and low quality on low adherence 71,40% . Result of statistical test usingChi Square obtained p value (0,037)>alpha (0,05), so that there is correlation between medicationadherence and quality of life of MDR Tb patient in polyTb-MDR RSUD Arifin Ahmad Riau Province.Key words: life quality, medical adherence, MMAS-8, Tb MDR, WHOQOL BREEF